Analisis Kesalahan Penulisan Ejaan Pada Pamflet dan Banner - Mhd Ahwadi Hasibuan; Nur Hakima Akhirani Nasution (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesian is a language that emerged from the efforts of our ancestors in the past. This language is recognized as the official language by the Indonesian nation, and today we still follow the General Guidelines for Indonesian Spelling (PUEBI). However, in practice, there are still mistakes in the use of Indonesian, especially in the placement of letters on banners, signage, and pamphlets around us. This article is written to identify spelling errors found on banners, signage, and pamphlets that can be found along the streets around us. The method used in this study is qualitative descriptive with data collection techniques through observation and documentation. The findings of this study show the existence of spelling mistakes on banners, signage, and pamphlets, which include letter writing, word writing, and the use of punctuation marks.